Applications of social network analysis in behavioural information security research: Concepts and empirical analysis. Issue 68 (July 2017) - Dang-Pham, Duy; Pittayachawan, Siddhi; Bruno, Vince
Abstract: The rapid digital transformation and technological disruption in modern organisations demand the development of people-centric security workplaces, whereby the employees can build up their security awareness and accountability for their actions via participation in the organisation's social networks. The social network analysis approach offers a wide array of analytical capabilities to examine in-depth the interactions and relations within an organisation, which assists the development of such security workplaces. This paper proposes the novel and practical adoption of social network analysis methods in behavioural information security field. To this end, we discuss the core features of the social network analysis approach and describe their empirical applications in a real case study of a large organisation in Vietnam, which utilised these methods to improve employees' information security awareness. Towards the end of the paper, a framework detailing the strategies for conducting social network analysis in the behavioural information security field is developed and presented.